THE INFLUENCE OF eWOM AND PERCEPTION OF PRICE ON PURCHASE INTENTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE IN KAHF CARE PRODUCTS - Irfan Syahputra; Paham Ginting; Arlina Nurbaity Lubis (CV. Radja Publika, 2023)
eWOM is a form of electronic word-of-mouth communication that includes reviews and recommendations. Price perception is the consumer's evaluation of a product's value in relation to its price. Brand image refers to consumers' perception of a product brand that is embedded in their minds. The sales percentage of Kahf Care products fluctuated between the years 2021 and 2022. This is due to the emergence of many local brands offering similar specialized grooming products for men. This study aims to analyze the influence of eWOM and the perception of price on purchase intention with brand image in Kahf Care products. The study examines 380 respondents who use Kahf Care products, selected through purposive sampling technique, and is tested using the statistical analysis method of path analysis. The results of the first substructure indicate that eWOM and price perception have a positive and significant impact on brand image. The results of the second substructure indicate that eWOM, price perception, and brand image have a positive and significant influence on purchase intention. There is a direct positive and significant influence of eWOM and perception of price on purchase intention. This research also shows that eWOM and price perception have an indirect positive and significant influence on purchase intention through brand image. Brand image acts as an intervening variable based on the Sobel test. and brand image has a positive and significant influence on purchase intention. There is a direct positive and significant influence of eWOM and perception of price on purchase intention. This research also shows that eWOM and price perception have an indirect positive and significant influence on purchase intention through brand image. Brand image acts as an intervening variable based on the Sobel test. and brand image has a positive and significant influence on purchase intention. There is a direct positive and significant influence of eWOM and perception of price on purchase intention. This research also shows that eWOM and price perception have an indirect positive and significant influence on purchase intention through brand image. Brand image acts as an intervening variable based on the Sobel test.